How does being out at work relate to discrimination and unemployment of gays and lesbians? - Karel Friéc (Journal for Labour Market Research, 2019)
This article empirically investigates the relationships in the workplace between homonegativity, the disclosure of sexual orientation, perceived discrimination, the reporting of discriminatory incidents and an individual's employment status. I utilize information reported by gays and lesbians in the EU lesbian, gay, bisexual and transgender (LGBT) survey. The data was analysed using generalised structural equation modelling and the logistic regression model. The results indicate that gays and lesbians conceal their sexual orientation more in hostile workplaces. A higher level of concealment is linked with an increased perception of discrimination and with a lower likelihood of reporting discriminatory incidents. Perceived discrimination and (unlike hypothesised) also concealment of sexual orientation positively relate to the probability of being unemployed. This implies a vicious circle in which hostile attitudes force gay employees to conceal their sexuality which in turn limits their ability to confront discriminatory behaviour.
Keywords: 330; Disclosure of sexual orientation; Discrimination; Homosexuality; LGBT; Unemployment